Therapeutic effect of intravenous levetiracetam in status epilepticus: A meta-analysis and systematic review. (January 2020) - Chu, Shan-shan; Wang, Hai-jiao; Zhu, Li-Na; Xu, Da; Wang, Xue-ping; Liu, Ling
Highlights: IV LEV appears to be as effective as PHT, VPA, and LOR for the treatment of SE. IV LEV as add-on therapy of CNP had no superiority in seizure cessation than CNP plus placebo. IV LEV may have a better tolerability profile than other AEDs do. More rigorous RCTs are required to determine the place of IV LEV in SE. Abstract: Purpose: We performed this analysis to evaluate the efficacy and safety of intravenous levetiracetam (IV LEV) in patients with status epilepticus. Method: Studies were searched in MEDLINE, EMBASE, and the Cochrane Central Register of Controlled Trials for available randomized controlled trials(RCTs) comparing the efficacy and/or safety of IV LEV with other antiepileptic drugs (AEDs). Meta-analysis was performed using the random-effects model to calculate risk ratio with the RevMan 5.3 software. Results: Six RCTs with a total of 543 patients were included. There was no significant differences in clinical seizure cessation and hospital mortality, either between IV LEV and IV phenytoin (PHT) or between IV LEV and IV valproate (VPA). Compared with IV PHT, IV LEV had a lower risk of poor neurological outcome. For IV LEV compared with IV lorazepam (LOR), no significant difference in efficacy was found, but IV LEV patients had significantly lower need for ventilatory assistance. Adding IV LEV to clonazepam (CNP), compared with adding placebo showed no significant differences in seizure cessation at 15 min. Conclusions: Our results suggested that IV LEV was comparable to IV PHT, VPA, or LOR in efficacy, and IV LEV as add-on therapy of CNP had no superiority in seizure cessation than CNP plus placebo. IV LEV may have a better tolerability than other AEDs do. More RCTs are needed to validate the role of IV LEV in status epilepticus.